The Competitive Advantages of Uber over its Direct Competition in the Private Transport Business in Guadalajara, Jal. - Bustamante-Hernández, Carlos S. (Ediciones UNL. Secretaría de Extensión de la UNL, 2019)
The aim of this article is to present information about the company Uber in Guadalajara, Jalisco, and its incursion into the Mexican private transport market. The method used is a bibliographic review and data base of the company on the positioning of UBER in the transport market of Guadalajara as a previous activity to perform a competitive analysis from a strategic and economic point of view. As a result of the analysis, the main factors that have made Uber one of the market leaders in the private transport business are described. Finally, some recommendations as regards the conflicts caused by the company’s entrance into a new market are made.